2018
DOI: 10.1038/s41467-018-04459-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of mRNA export regulation by the nuclear pore complex

Abstract: The nuclear pore complex (NPC) controls the passage of macromolecules between the nucleus and cytoplasm, but how the NPC directly participates in macromolecular transport remains poorly understood. In the final step of mRNA export, the DEAD-box helicase DDX19 is activated by the nucleoporins Gle1, Nup214, and Nup42 to remove Nxf1•Nxt1 from mRNAs. Here, we report crystal structures of Gle1•Nup42 from three organisms that reveal an evolutionarily conserved binding mode. Biochemical reconstitution of the DDX19 AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 68 publications
3
77
0
Order By: Relevance
“…Structure of the human DDX19•GLE1•NUP42 complex reveals that NUP42 does not contact DDX19 directly, and causes no significant conformational change in GLE1 (Figure F) . The effect of NUP42 is suggested to be attributed to increasing GLE1 thermostability; the melting temperature of GLE1 increased from 37 to 50 °C in the presence of NUP42 . Of note, in the human DDX19•GLE1•NUP42 complex, only DDX19‐CTD is engaged in GLE1 binding, whereas Gle1 contacts both Dbp5 NTD and CTD in the yeast Dbp5•Gle1•IP 6 complex.…”
Section: Disassembly Of the Mrnp Export Complexmentioning
confidence: 99%
See 3 more Smart Citations
“…Structure of the human DDX19•GLE1•NUP42 complex reveals that NUP42 does not contact DDX19 directly, and causes no significant conformational change in GLE1 (Figure F) . The effect of NUP42 is suggested to be attributed to increasing GLE1 thermostability; the melting temperature of GLE1 increased from 37 to 50 °C in the presence of NUP42 . Of note, in the human DDX19•GLE1•NUP42 complex, only DDX19‐CTD is engaged in GLE1 binding, whereas Gle1 contacts both Dbp5 NTD and CTD in the yeast Dbp5•Gle1•IP 6 complex.…”
Section: Disassembly Of the Mrnp Export Complexmentioning
confidence: 99%
“…In the mRNA export platform, Gle1, IP 6 (inositol hexakisphosphate) and Nup42 provide spatial and temporal regulation of Dbp5 by stimulating its ATPase activity (Figure B). Dbp5 contains two RecA‐like domains (NTD and CTD) and a short N‐terminal extension (NTE).…”
Section: Disassembly Of the Mrnp Export Complexmentioning
confidence: 99%
See 2 more Smart Citations
“…A limited set of studies have also shown that aside from XPO5, the export of few precursor miRNAs occurs through XPO1 as well (10). The mRNAs have a distinct export mechanism that occurs with the help of adaptor serine/arginine rich proteins that promote the recruitment of heterodimeric mRNA export receptor NXF1-NXT1 which facilitates exit through the nuclear pore (11). Despite some available knowledge on microRNA nuclear transport, the non-coding RNA nuclear transport in general remains an under-studied field.…”
mentioning
confidence: 99%